The association between peripheral total IGF-1, IGFBP-3, and their molar ratio levels and functional and cognitive outcomes in the Mayo Clinic Study of Aging - Wennberg, Alexandra M.V. (Neurobiol Aging, 2018)
Levels of insulin-like growth factor (IGF)-1, IGF binding protein (IGFBP)-3, and their ratio in the blood may be useful for monitoring those at risk of cognitive and functional decline. However, the association between IGF measures and functional and cognitive outcomes has been mixed, and the associations may vary by sex. The present study investigated the cross-sectional, sex-specific associations between serum measures total IGF-1, IGFBP-3, and the IGF-1/IGFBP-3 ratio, gait speed, and cognition in 1,320 cognitively unimpaired participants aged 50-95 enrolled in the Mayo Clinic Study of Aging. We utilized multivariable linear regression models to determine the association between IGF measures and gait speed or cognitive test performance by sex. IGF measures were not associated with cognitive or functional performance among men. Among women, higher levels of log total IGF-1 and IGFBP-3 were associated with better performance in attention, visuospatial, and global cognitive domains, independent of gait speed. These findings suggest that among women IGF measures are associated with cognition, and these associations are independent of function.